Teacher Guidance And Counseling Strategy In Handling Bullying Behavior At SMP Negeri 1 Balongan - Siti Aisyah (Beginner: Journal of Teaching and Education Management, 2023)
Bullying is the act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels pressured, traumatized and helpless. Teenagers who experience acts of bullying are at greater risk than perpetrators, including experiencing mental health problems such as depression, anxiety and abnormal sleep problems that can carry over into adulthood. The purpose of this study was to describe and provide a prevention to overcome bullying behavior in SMP Negeri 1 Balongan. This research uses descriptive qualitative research by collecting data in the field by providing a statement from the results of the class 8A, 8C, 8E sample with a total of 88 students and from relevant sources. The guidance and counseling teacher's strategy for overcoming bullying behavior in SMP Negeri 1 Balongan schools is by providing a service, namely group guidance to students to overcome bullying in the school environment so that students can implement it in everyday life